TPACK to GPACK? The examination of the technological pedagogical content knowledge framework as a model for global integration into college of agriculture classrooms. (July 2018) - Urban, Emily R.; Navarro, Maria; Borron, Abigail
Abstract: Faculty in U.S. colleges of agriculture are encouraged to internationalize their classroom curricula, but further research is needed to determine how to best prepare faculty. This study explores the transferability of the technological pedagogical content knowledge model (TPACK), originally used for technology integration, to our proposed model, the global pedagogical content knowledge model (GPACK), for the effective integration of global concepts into content-specific courses. Interviews from eight program participants of a yearlong faculty development program imply combined faculty training in global issues, pedagogy, and content, rather than in an exclusive knowledge area, may more adequately prepare faculty for classroom internationalization. Highlights: Exploring the TPACK framework for global integration, or internationalization. Global knowledge alone does not lead to effective internationalization of curriculum. Determining the suitability of the GPACK model for faculty development programs. International travel component was integral for interlinking knowledge groups of GPACK.